Social Cohesion in Times of Crisis: The Corona Pandemic and anti-Asian Racism in Germany: Internal Perspective - Suda, Kimiko (Deutsches Zentrum für Integrations- und Migrationsforschung DeZIM, 2024)
The project “Social Cohesion in Times of Crisis: The COVID-19 Pandemic and Anti-Asian Racism in Germany" examined the extent to which the COVID-19 pandemic has affected racism against people perceived as Asian in Germany. It was a cooperation project between Humboldt-Universität zu Berlin, Free University of Berlin, and the German Center for Integration and Migration Research (DeZIM) and was funded as part of the "Grand Challenges: Pandemic" special call by the Berlin University Alliance (BUA). The project followed a mixed-methods design, resulting in two quantiative surveys and a qualitative diary study. External Perspective: Within the "External Perspective" study, a quantitative online survey with experimental elements was conducted in three waves to explore the overall societal perspective on the central research question. This study aimed to investigate the social-psychological factors that promote anti-Asian racism. For the study, 4843 fully realized interviews were conducted in wave1, 3818 in wave2, and 2603 in wave3. The field periods was November/December 2020 (wave1), January/February 2021 (wave2) and May/Juni 2021 (wave3). The study design and online survey instruments were developed by the project team. The practical execution of the pretest and the three-wave study was carried out by respondi AG. Community Survey: Additionally, a nationwide self-recruited online community survey (convenience sample) was carried out, which was fully answered by 703 people of Asian origin. The aim of the survey was to record the experiences of people of Asian origin at the beginning of the Covid-19 pandemic. The survey focuses the extent, forms, places, consequences of anti-Asian racism as well as coping strategies during the pandemic from the perspective of people of Asian origin in Germany. The field period was October to December 2020. The survey instruments were developed by the project team and the online survey was conducted self-administrated (LimeSurvey).